Analisis kepuasan ibu hamil terhadap kualitas pelayanan pemeriksaan kehamilan dikaitkan dengan biaya tambahan di Puskesmas Bukit Hindu = satisfaction analysis of pregnant mothers on the service quality of pregnancy check - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Background: In providing basic health services, community health center often experiences budget shortage to develop its service quality, due to budget constraint for operational activities. To cover cost. "l3ukit Hindu" health center charged additional fee to improve the pregnancy check-up service. This study examined the level of satisfaction among pregnant mothers toward pregnancy check-up service in relation with additional service cost. Methods: This was a non-experimental study using cross-sectional approach. The subjects were health services at maternal and child health (KIM room, with pregnant mother as unit of analysis. Questionnaires were distributed to 201 pregnant mothers from April I to April 21, 1999 Results: Result showed that: (a) additional cost significantly affected satisfaction of health service quality, and satisfaction was influenced by age, education, income, and frequency of pregnancy treatment